Intestinal flora and bile acid interactions impact the progression of diabetic kidney disease - Xu, Jia; Wang, Nan; Yang, Li; Zhong, Jing; Chen, Ming (Frontiers in Endocrinology, 2024)
In recent years, with the rapid development of omics technologies, researchers have shown that interactions between the intestinal flora and bile acids are closely related to the progression of diabetic kidney disease (DKD). By regulating bile acid metabolism and receptor expression, the intestinal flora affects host metabolism, impacts the immune system, and exacerbates kidney injury in DKD patients. To explore interactions among the gut flora, bile acids and DKD, as well as the related mechanisms, in depth, in this paper, we review the existing literature on correlations among the gut flora, bile acids and DKD. This review also summarizes the efficacy of bile acids and their receptors as well as traditional Chinese medicines in the treatment of DKD and highlights the unique advantages of bile acid receptors in DKD treatment. This paper is expected to reveal a new and important potential strategy for the clinical treatment of DKD.